'A great list of potential mistakes': NATO, Africa, and British efforts to limit the Global Cold War. Issue 1 (2nd January 2016) - Sayle, Timothy Andrews
Abstract : The scholarly consensus on why NATO adopted a 'non-policy' towards the non-North Atlantic world rests on the logic of the Cold War. But British diplomats and officials did not see NATO's policy towards Africa through a Cold War lens. NATO's 'non-policy' towards the world beyond the North Atlantic was not the product of an allied Cold War consensus among the allies. Instead, it was the result of a determined British effort to channel growing pressure for NATO action into a bureaucratic dead-end in an effort to keep the Cold War out of Africa.